BOARD-AI: A goal-aware modeling interface for systems engineering, combining machine learning and plan recognition - Castellanos-Paez, Sandra; Hili, Nicolas; Albore, Alexandre; Pérez-Sanagustín, Mar (Frontiers in Physics, 2022)
Paper and pens remain the most commonly used tools by systems engineers to capture system models. They improve productivity and foster collaboration and creativity as the users do not need to conform to formal notations commonly present in Computer-Aided Systems Engineering (CASE) tools for system modeling. However, digitizing models sketched on a whiteboard into CASE tools remains a difficult and error-prone activity that requires the knowledge of tool experts. Over the past decade, switching from symbolic reasoning to machine learning has been the natural choice in many domains to improve the performance of software applications. The field of natural sketching and online recognition is no exception to the rule and most of the existing sketch recognizers rely on pre-trained sets of symbols to increase the confidence in the outcome of the recognizers. However, that performance improvement comes at the cost of trust. The lack of trust directly stems from the lack of explainability of the outcomes of the neural networks, which hinders its acceptance by systems engineering teams. A solution shall not only combine the performance and robustness but shall also earn unreserved support and trust from human users. While most of the works in the literature tip the scale in favor of performance, there is a need to better include studies on human perception into the equation to restore balance. This study presents an approach and a Human-machine interface for natural sketching that allows engineers to capture system models using interactive whiteboards. The approach combines techniques from symbolic AI and machine learning to improve performance while not compromising explainability. The key concept of the approach is to use a trained neural network to separate, upstream from the global recognition process, handwritten text from geometrical symbols, and to use the suitable technique (OCR or automated planning) to recognize text and symbols individually. Key advantages of the approach are that it does not resort to any other interaction modalities (e.g., virtual keyboards) to annotate model elements with textual properties and that the explainability of the outcomes of the modeling assistant is preserved. A user experiment validates the usability of the interface.